‘Hellenistic’ House in Nea Paphos, Cyprus – A First Summary of Its Architecture - Brzozowska-Jawornicka, Aleksandra (Études et Travaux, 2021)
This paper presents preliminary observations and analyses of the architecture of the ‘Hellenistic’ House, an ancient residency from Roman times built in Nea Paphos on Cyprus. The House was erected as an extensive edifice around several courtyards of a very interesting architectural frame and rich decoration. Unfortunately, the residence was destroyed by an earthquake and afterwards rebuilt with new edifices, primarily the Villa of Theseus, and as such its remains are in a very poor state. However, the preserved fragments of walls, floors, technical infrastructure as well as pieces of architectural decoration permit the conducting of architectural studies of the residence’s layout, structure and functional arrangement.